Measuring the Technical Efficiency of Insurance Companies in Jordan Using (DEA) During the Period (2000-2016) - Jaloudi, Mutasem; Bakir, Amer (Jordan Journal of Economic Sciences, 2019)
This study aimed to evaluate the insurance companies in Jordan during the period 2000-2016 by measuring the technical efficiency of these companies. The study uses panel data for (22) insurance companies operating in Jordan, where the technical efficiency were estimated by utilizing Data Envelopment Analysis (DEA). The study indicated that there were differences in the technical efficiency of the insurance companies in Jordan during the study period, ranging from 72.5% to 100%. The results also showed that owners’ equity are among the most important determinants of companies’ efficiency, followed by technical provisions and operating expenses. Its also noticed that high-efficiency companies focused on one class of insurance, unlike low-efficiency companies with a diversified insurance portfolio. The study recommends improving the technical efficiency for low-efficiency companies by reducing the level of inputs used, reallocating the resources used, and focus on specific class of insurance to maximize efficiency.